Ommatophoca rossu Gray 1844 - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
8. Ross Seal Ommatophoca rossu French: Phoque de Ross / German: Ross-Robbe / Spanish: Foca de Ross Other common names: Bigeyed Seal, Ross's Seal, Singing Seal Taxonomy. Ommatophoca rossi Gray, 1844, “Antarctic ocean.” Restricted by G. E. H. Barrett-Hamilton in 1902 to “pack ice, north of Ross Sea 68°S, 176°E.” This species is monotypic. Distribution. Circumpolar in the Southern Ocean. Descriptive notes. Total length 170-210 cm (males) and 190-250 cm (females); weight 129-216 kg (males) and 159-201 kg (females). Newborns are 105-120 cm in length and weigh 17-27 kg. Ross Seals have relatively small but robust bodies with short, broad heads. Eyes are noticeably large and forward pointing, reflecting adaptations to their deep diving and foraging habits. Teeth are all small, and post-canines are simple without shearing or grinding structure. Canine teeth are very sharply conical, apparent adaptations for catching squid that seem to be their primary prey. Short pelage is dark brown dorsally and cream or tan ventrally, with several dark stripes radiating down throat from mouth and some spotting along boundary between counter-shaded, dorsal-ventral pattern. Ross Seals molt in late December—January and perhaps into mid-February. Habitat. Confined to the Southern Ocean and sparsely distributed around the Antarctic Continent. In late autumn and early summer, breeding Ross Seals are distributed in heavily consolidated pack ice in the Ross, Amundsen, and Bellingshausen seas of West Antarctica and scattered around East Antarctica and perhaps in the western Weddell Sea. From late summer through early autumn, Ross Seals appear to be pelagic, spending most of their time north of sea-ice habitats and foraging at relatively deep depths of 200-500 m or more. Most sightings of Ross Seals have been ofsolitary individuals, but small groups and aggregations have been seen a few times. Some of these aggregations and groups were recorded in areas of sparse ice and evidently reflected absence of suitable sites to haul-out. Vagrant Ross ...